Potential drug interactions related to antimicrobials use in hospitalized patients on hemodialysis - Pryscila R. MOREIRA; Leonardo T. FARIAS; Cristiane C. SANTOS; Elza A. DOMINGUES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: to evaluate the prevalence, severity and main clinical consequences of potential drug interactions (DIs) related to antimicrobials in hemodialysis patients admitted to a university hospital. Methods: This is an observational and retrospective study, conducted in a university hospital in the Midwest region, the sample consisted of adult patients using antimicrobial therapy and undergoing renal replacement therapy. DIs were verified in medical prescriptions, during a period of 7 days, using the Micromedex® database. Results: 85 patients were included in the study and 595 prescriptions were analyzed. As for kidney disease, 30 (35.3%) of the patients underwent hemodialysis for acute kidney injury, 45 (53%) for chronic kidney disease and in 10 (11.7%) it was not possible to verify the type of kidney disease due to lack of information in the charts. At least one DI were identified in 29.6% of prescriptions. In all, 499 interactions were found, of which 301 (60.3%) were important, 149 (29.9%) were moderate and 49 (9.8%) were contraindications. Regarding possible adverse events related to contraindicated interactions, 25 (51.0%) were related to an increase in hypertensive events and 8 (16.3%) to cardiotoxicity. The antimicrobials most involved in possible DI were fluconazole (98.76% of antifungals), ciprofloxacin (79.4% of quinolones) and linezolid (oxazolidones). The most frequent interactions were: linezolid and norepinephrine (contraindicated), ciprofloxacin and insulin (important), fluconazole and fentanyl (important), fluconazole and omeprazole (moderate). Conclusion: Most of the potential DIs identified were serious and there was a high percentage of contraindicated DIs. The main potential adverse events were related to the cardiovascular system. These findings reinforce the importance of knowing the possible antimicrobial-related DIs in hemodialysis patients, their possible adverse events and corresponding management.